Research of Condensate Resistance Measurement Using Single-Contact Substrate - Jukna, Tomas; Sinkevicius, Vytenis; Urbanaviciute, Lina; Valickas, Jonas (Elektronika ir Elektrotechnika, 2016)
The research of non-invasive method for condensate resistance measurement uses a substrate with a single-contact area. The novelty of this measurement method lies in the use of electrical current of electrons emitted during the process of electronic emission from an evaporator. Therefore, there is no need of any additional current or voltage source. This study develops a mathematical model describing the performance and dependencies of this method of measurement. The adequacy of this mathematical model was investigated experimentally. For this purpose, the results of direct measurement of substrate condensate resistance were used. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.14107